2022
DOI: 10.3390/rs14246345
|View full text |Cite
|
Sign up to set email alerts
|

UAV-Based Estimation of Grain Yield for Plant Breeding: Applied Strategies for Optimizing the Use of Sensors, Vegetation Indices, Growth Stages, and Machine Learning Algorithms

Abstract: Non-destructive in-season grain yield (GY) prediction would strongly facilitate the selection process in plant breeding but remains challenging for phenologically and morphologically diverse germplasm, notably under high-yielding conditions. In recent years, the application of drones (UAV) for spectral sensing has been established, but data acquisition and data processing have to be further improved with respect to efficiency and reliability. Therefore, this study evaluates the selection of measurement dates, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 64 publications
5
14
0
Order By: Relevance
“…Considering the limited studies on GY modelling for predicting genotypic differences in GY in different locations and years, this analysis aims to evaluate the dataset effect for GY prediction in winter wheat breeding yards based on data from three years and two locations. It extends the evaluation of within-trials models from two locations and two years [19]. This study recommended a red edge index amongst different RGB and multispectral indices and measurements around anthesis and early milk ripeness.…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…Considering the limited studies on GY modelling for predicting genotypic differences in GY in different locations and years, this analysis aims to evaluate the dataset effect for GY prediction in winter wheat breeding yards based on data from three years and two locations. It extends the evaluation of within-trials models from two locations and two years [19]. This study recommended a red edge index amongst different RGB and multispectral indices and measurements around anthesis and early milk ripeness.…”
Section: Introductionmentioning
confidence: 84%
“…The methodology is based on that described in detail in Prey et al (2022) [19]. Based on that study [19], which identified the normalized difference red edge index (NDRE1) as overall best vegetation index for GY estimation among several tested multispectral and RGB bands and vegetation indices, this study focuses on this spectral index. The index was calculated as…”
Section: Postprocessing Of Spectral Data and Grain Yield Modellingmentioning
confidence: 99%
See 3 more Smart Citations